CasEcR and CasMIH Genes in the Blue Crab, Callinectes sapidus: A Temporal Evaluation and Melatonin Effects - David, Daniela Dantas; de Assis, Leonardo Vinícius Monteiro; Moraes, Maria Nathalia; Zanotto, Flávia Pinheiro; Castrucci, Ana Maria de Lauro (Frontiers in Physiology, 2022)
Environmental cues synchronize endogenous rhythms of many physiological processes such as hormone synthesis and secretion. Little is known about the diurnal pattern of hormones and gene expression of the Callinectes sapidus molt cycle. We aimed to investigate in the eyestalk and hepatopancreas of premolt and intermolt C. sapidus the following parameters: (1) the diurnal expression of the ecdysteroid receptor CasEcR isoforms, and the molt inhibiting hormone CasMIH; (2) the diurnal hemolymph ecdysteroid and melatonin levels; and (3) melatonin effects on the transcripts of the above-mentioned genes in intermolt C. sapidus. Ecdysteroid levels were higher in the premolt than the intermolt animals at all time points evaluated (ZTs). Premolt crabs displayed a variation of ecdysteroid concentration between time points, with a reduction at ZT17. No difference in the melatonin level was seen in either molt stage or between stages. In the eyestalk of intermolt animals, CasEcR expression oscillated, with a peak at ZT9, and premolt crabs have a reduction at ZT9; CasMIH transcripts did not vary along 24 h in either molt stage. Moreover, the evaluated eyestalk genes were more expressed at ZT9 in the intermolt than the premolt crabs. In the hepatopancreas, CasEcR expression showed a peak at ZT9 in premolt crabs. Exogenous melatonin (10-7 moles/animal) reduced the expression of both genes in the eyestalk at ZT17. In the hepatopancreas, melatonin markedly increased the expression of the CasEcR gene at ZT9. Taken altogether, our results are pioneer in demonstrating the daily oscillation of gene expression associated to molt cycle stages, as well as the daily ecdysteroid and melatonin levels and the remarkable influence of melatonin on the molt cycle of C. sapidus.